38 Londres Street: On Impunity, Pinochet in England and a Nazi in Patagonia by Philippe Sands review – war crimes revisited - Anthony, Andrew (The Guardian, 2025)
In the final part of a bravura trilogy detailing the struggle to bring war criminals to account, Sands tracks a former SS commander to Chile, where he found a friend in Augusto Pinochet
Chile
Keywords: Augusto Pinochet; Books; Culture; History books; Law; Philippe Sands; War crimes